Case report: genetic analysis of a novel frameshift mutation in FMR1 gene in a Chinese family - Jin, Chunlei; Zhang, Xiangdong; Lei, Qiang; Chen, Penglong; Hu, Hui; Shen, Shuangshuang; Liu, Jiao; Ye, Shixuanbao (Frontiers in Genetics, 2023)
Fragile X syndrome (FXS) [OMIM 300624] is a common X-linked inherited syndrome with an incidence only second to that of trisomy 21. More than 95% of fragile X syndrome is caused by reduced or absent fragile X intellectual disability protein 1 (FMRP) synthesis due to dynamic mutation expansion of CGG triplet repeat in the 5'UTR and abnormal methylation of the FMR1 (fragile X messenger ribonucleoprotein 1) gene [OMIM 309550]. Less than 5% of patients are caused by abnormal function of the FMRP due to point mutations or deletions in the FMR1 gene.In a proband in a pedigree with clinical suspicion of FXS and no CGG duplication, we found the presence of c.585_586del (p.Lys195AsnfsTer8) in exon 7 of the FMR1 gene using whole exome sequencing (WES). This variant resulted in frameshift and a premature stop codon after 8 aberrant amino acids. This variant is a novel pathogenic mutation by pedigree analysis, which has not been reported in any database or literature.